First trimester maternal serum pregnancy-associated plasma protein-A is a predictive factor for early preterm delivery in normotensive pregnancies. (June 2013) - Dane, Banu; Dane, Cem; Batmaz, Gonca; Ates, Seda; Dansuk, Ramazan
Abstract In this study, we investigated whether the concentrations of pregnancy-associated plasma protein-A (PAPP-A) or free β-hCG (fβhCG) in the first trimester can identify women at increased risk of subsequent preterm delivery in the absence of hypertensive disorders. Preterm and early preterm deliveries are defined as those deliveries before completing 37 and 34 weeks, respectively. A total of 868 women were enrolled into this study. According to the level of the markers, the patients were evaluated in three groups: 1 – maternal serum level ≤5th percentile, 2 – between 5th and 95th percentiles, 3 – ≥95th percentile. In the group of patients with a PAPP-A level ≤5th percentile [≤0.35 multiples of the median (MoM)], mean gestational age (GA) at delivery, mean birth weight and the number of the cases with early preterm delivery were significantly lower than the others. Mean level of PAPP-A was significantly lower in cases with early preterm than term deliveries (0.58 ± 0.32 versus1.09 ± 0.69; p = 0.01). Maternal serum level of fβhCG did not show significant difference between these groups (0.84 ± 0.45 versus 1.17 ± 0.77; p = 0.15). Low levels of maternal serum PAPP-A (≤0.35 MoM) (Odds ratio = 7; 95% confidence interval 1.8–27.7; p = 0.0048) significantly predicted early preterm delivery in normotensive pregnancies. Women with low levels of PAPP-A at first trimester have a higher risk of early preterm delivery even in the absence of hypertensive disorders.